Theological Foundations for Collaborative Ministry - Pickard,Stephen (Surrey Ashgate Publishing Limited, 2009)
This book examines the theological foundations of a collaborative approach to Christian ministry. The discovery that Christians are members 'one of another' creates energy and joy in ministry and empowers the Church in an age of mission. Outlining the p
Keywords: Cooperative ministry. Group ministry. Church management